PELAKSANAAN KEBIJAKAN PEMERINTAH DAERAH DALAM PENGELOLAAN SAMPAH DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI TAHUN 2018 - Putri Ayu Pratama; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Meranti Islands Regency Environmental Service is a government agency that has the authority to carry out government affairs in the environmental sector, one of which is in the field of waste management. Waste management is a systematic, comprehensive and continuous activity which includes waste reduction and handling. The population growth in Tebing Tinggi Subdistrict, Kepulauan Meranti Regency, which is getting higher causes the waste generated every day to always increase due to changes in consumption patterns and people's lifestyles, so that waste piles increase so that special handling is needed for waste management carried out by the Environmental Service.The purpose of this study is to explain the implementation of local government policies on waste management in Tebing Tinggi District, Meranti Islands Regency in 2018 and the inhibiting factors that affect the waste management. The research methodology uses a qualitative approach with descriptive research type. This method aims to get a correct picture of explaining the implementation of local government policies on waste management in Tebing Tinggi District, Meranti Islands Regency.The result of this research is that the implementation of local government policies in waste management carried out by the Environment Agency of Meranti Islands Regency as an effort to reduce and handle waste has not been optimal. In the aspect of waste reduction, the activities for limiting waste generation are not optimal, recycling of waste has limited facilities and infrastructure, the use of community waste that produces waste does not participate in the process of reusing waste, in the aspect of waste management, sorting activities have not been implemented, activities for collecting locations that will be used Until now, there is no garbage disposal site (TPS), there is not enough waste transportation fleet, waste processing activities do not have environmentally friendly technological infrastructure, and final processing activities are still carried out by means of open dumpling. As for the inhibiting factors for the implementation of waste management, the organizational capabilities are still inadequate, the lack of information provided to the public, the lack of budget support and the distribution of potentials that has not been optimal.  Keywords: Organizational Capabilities, Information, Support, Potential Sharing